ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DENGAN POLA TANAM TABELA DI DESA DOLAGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Nasarudin, Akram; Muis, Abdul (AGROTEKBIS, 2016)
The study aimed to determine the influence of land, seed, fertilizer, labor and income of direct seeding wetland rice farming system on its rice production in Dolago village, South Parigi subdistrict of Parigi Moutong District. The experiment was conducted from December 2015 to February 2016. The results showed that the land area (X1), the seeds (X2), fertilizers (X3) and the labor (X4) had simultaneously significant effect on the production of the direct seeding wetland rice farming system. This is indicated by the F-counted equal to 262.585> F-table 3.828 at Î± level of 1% suggesting the acceptance of H1. Partially the land area, the seeds, and the fertilizer are highly significant as shown by their t-counted of 8.35, 5.959, and 3.334, respectively are > t-table (2.423) at Î± level of 1% while the labor is significant (t-counted (2.235)> t-table (1.684) at Î± level of 5%. The average income of the respondent farmers is IDR 24,308,874.35/1.13 ha or IDR 21,449,006.79/ha.Â Key Words : Production, income, wetland rice.